Analysis of the interaction effect of 48 SNPs and obesity on type 2 diabetes in Chinese Hans. Issue 2 (17th November 2020) - Liu, Jia; Wang, Lu; Qian, Yun; Shen, Qian; Chen, Hai; Ma, Hongxia; Dai, Juncheng; Shen, Chong; Jin, Guangfu; Hu, Zhibin; Shen, Hongbing
Abstract : Introduction: Both environmental and genetic factors contribute to type 2 diabetes (T2D) risk. Dozens of T2D susceptibility loci have been identified by genome-wide association study. However, these loci account for only a small fraction of the familial T2D risk. We hypothesized that the gene-obesity interaction may contribute to the missing heritability. Research design and method: Forty-eight T2D-associated variants were genotyped using the TaqMan OpenArray Genotyping System and iPLEX Sequenom MassARRAY platform in two separate studies. Obesity was defined according to multiple indexes (body mass index (BMI), waist circumference and waist-hip ratio). Multiplicative interactions were tested using general logistic regression to assess the gene-obesity interaction effect on T2D risk among a total of 6206 Chinese Hans. Results: After adjusting for the main effects of genes and obesity, as well as covariates (age, sex, smoking and alcohol consumption status), robust multiplicative interaction effects were observed between rs10811661 in CDKN2A/CDKN2B and multiple obesity indices (p ranged from 0.001 to 0.043 for BMI, waist circumference and waist-hip ratio). Obese individuals with the TT genotype had a drastically higher risk of T2D than normal weight individuals without the risk allele (OR=17.58, p<0.001). There were no significant differences between subgroups in the stratification analysis. Plausible biological explanations were established using a public database. However, there were no significant interaction effects between the other 47 single nucleotide polymorphism (SNPs) and obesity. Conclusion: Our findings indicated that the CDKN2A/CDKN2B gene-obesity interaction significantly increases T2D risk in Chinese Hans. The interaction effect identified in our study may help to explain some of the missing heritability in the context of T2D susceptibility. In addition, the interaction effect may play a role in the precise prevention of T2D in Chinese individuals.